Student perceptions of digital resources in social science learning (Revista Electrónica REDINE, 2026)
The present study analyzes eighth-grade students’ perceptions of the use of digital resources in learning Social Studies, specifically in content related to the History of the Americas, at a secondary education institute in the city of Estelí, Nicaragua. The study adopts a qualitative approach, with a descriptive level and a non-experimental, cross-sectional design grounded in the interpretive paradigm. The population consisted of 255 eighth-grade students distributed across three sections during the second semester of the 2025 academic year; however, the study subjects were 35 students selected from one of the sections. For data collection, semi-structured interviews were conducted with teachers, a focus group was held, and an open-ended questionnaire was administered to students; these instruments had been previously validated by expert judgment. The data analysis was conducted through systematization, coding, and interpretive analysis processes. The results show that students frequently use artificial intelligence platforms, digital design tools, and interactive resources, which they associate with greater classroom participation and a more dynamic understanding of historical content. Likewise, the findings demonstrate that the integration of digital resources is linked to collaborative learning practices and to the development of students’ communicative, reflective, and analytical competencies. These results provide relevant insights to guide pedagogical decisions in teaching social studies at the secondary education level.
Keywords: technology; perception; social sciences; American history